Performance of rubber tree crown and panel clones in the southwest of the state of Mato Grosso, Brazil - Moraes, Vicente Haroldo de Figueiredo; Moraes, Larissa Alexandra Cardoso; Moreira, Adônis; Souza, Nilson Pereira de; Yokoyama, Roberto; Pereira, Ailton Vitor; Fialho, Josefino de Freitas (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the performance of 12 combinations ​​of three rubber tree panel clones (PB 311, PB 314, and RRIM 600) and four crown clones (F 4512, MDF 180, IAN 6158, and IAN 6543) grown in the southwest of the state of Mato Grosso, Brazil. A randomized complete block design was used, with four replicates. The following were evaluated: dry rubber yield, percentage of tappable trees, tapping panel dryness, nutritional status, dry rubber content, Wallace plasticity (P0 and P30), plasticity retention index, and Mooney viscosity. The combinations of the crowns IAN 6543 and MDF 180 with the panels PB 311, RRIM 600, and PB 314 showed adequate nutritional status, with dry rubber yield greater than 1.41 Mg ha-1 per year. The crown clone IAN 6158 provided, over eight years, the highest number of plants suitable for tapping. The panel/crown combinations showed low incidence of tapping panel dryness, except PB 311 x IAN 6158. The rubber of the 12 panel/crown combinations shows good resistance to thermal degradation and high plasticity retention.